Translation Strategy Application on the Indonesian Website-Based Texts into the English Website-Based Texts - Kristianto Setiawan (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2015)
AbstractThis research discusses two of the strategies proposed by Machali which are applied by the translators in translating the Indonesian news texts on the official website of The Indonesian Republic Government Secretariat into the English news texts on the same website. The strategies are transposition and modulation. Research statements of this research are (1) how is the transposition strategy in translating the texts on the official website of The Indonesian Republic Government Secretariat Ministry (2) how is the modulation strategy in translating the texts on the official website of The Indonesian Republic Government Secretariat Ministry. The data collection method in this research are reading and note taking methods that are reading and taking notes the data based on Machaliâ€™s strategies. Then, the collected data are analyzed by identifying the transposition and modulation strategies applied by the translators and described them in words. From the analysis of the data the researcher concludes that in translating theÂ Indonesian source texts into the English target texts, the translators apply the two strategies or procedures among the five strategies proposed by Machali. They are transposition and modulation. Transposition strategy is more dominant than modulationÂ strategy.Keywords: strategy, translation, transposition, modulation, accuracy